Beneficial additive values of wastewater irrigation of two aromatic plants grown in low fertile soil. Issue 1 (1st January 2020) - Elsokkary, Ibrahim H.; Aboukila, Alaa F.
ABSTRACT: The design of this study was to analyze the influence of irrigation by freshwater (FW) or by treated wastewater (TWW) on the growth and essential oil components in two aromatic plants: basil ( Ocimum basilicum L.) and oregano ( Origanum marjourm L.) grown in low fertile calcareous soil. A pot experiment was carried out in the greenhouse. The seeds of basil and oregano were sown and irrigated by either FW or TWW and harvested after 70 days from sowing for analysis. Tests between-subject effects point out there is a significant difference (p < 0.05) between the two forms of irrigation water on shoot yield, the yield of the flowering shoot, the quantity of essential oil, and some element concentrations in leaves of plants (N, P, Cu, Fe, and Mn), while there is no significant difference between essential oil percentage, K and Zn content. The obtained results specified that the essential oil yield significantly increased, as a result of irrigation by TWW from 0.58 to 1.08 in basil and from 2.00 to 3.06 ml 100 g −1 dry matter in oregano. Irrigation by TWW influenced the percentages of the essential oil components, whether positively or negatively, with reference to those produced by FW irrigation. The highest value of relative increase (719%) was that of d-Camphor (oxygenated monoterpene) in basil leaves and the lowest value of relative decrease (83%) was detected in basil leaves for methyl eugenol (oxygenated monoterpene). Regarding oregano; the highest and lowest values were 82% and 55% for p-Cymene (monoterpene hydrocarbons) and terpinolene (monoterpene hydrocarbons) respectively. These results provide significant beneficial additions due to irrigation of low fertile calcareous soil by treated wastewater to produce high valued essential oils from aromatic plants.